Stress and risk for depression in competitive athletes suffering from back pain – Do age and gender matter?†. Issue 7 (9th August 2018) - Belz, Johanna; Heidari, Jahan; Levenig, Claudia; Hasenbring, Monika; Kellmann, Michael; Kleinert, Jens
Abstract: Back pain (BP), a prominent problem for competitive athletes, is a primary reason for limitations in athletic performance and daily life restrictions. As studies on the relationship between psychological variables and BP in athletes are scarce, the aim of this study was to investigate stress and depression in competitive athletes with BP. In a cross-sectional design, data of 154 competitive athletes (51% female; M age  = 18.81 years, SD age  = 5.05 years) were collected, assessing Performance stress, Socio-emotional stress, Risk for depression and Psychological well-being and the two BP parameters BP Intensity and Disability . Two multiple linear regressions were conducted to predict (1) BP Intensity and (2) Disability from Performance stress, Socio-emotional stress, Risk for depression and Psychological well-being . Multiple linear regressions demonstrated that Performance stress ( β  = .21, p  = .01) was the only significant predictor of BP Intensity ( F 1, 142  = 6.68, p  = .01, R 2  = .05), whilst Risk for depression ( β  = .24, p  = .01) was the only significant predictor of Disability ( F 1, 142  = 8.46, p  = .01, R 2  = .06). Neither gender nor age explained a significant amount of variance in the models. Study results showed that, as in the general population, the variables stress and depression are related to BP in competitive athletes. In particular, BP intensity was found to be associated with stress and BP-related disability was associated with depression, whereas age and gender showed no association with the BP parameters. A longitudinal investigation is warranted to determine the direction of the observed relationships.